THE EFFECT OF VIDEO AND SIMULATION COUNSELLING ON CHILDREN'S KNOWLEDGE ABOUT HAND WASHING USING SOAP IN THE PRIVATE VOCATIONAL SCHOOL OF LAMBANDIA DISTRICT EAST KOLAKA DISTRICT: Counselling about hand washing using soap - Nur Ahmad; Tasnim Tasnim; Herianto Wahab (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Washing hands with soap is wrong for school children due to the child's lack of knowledge which is caused by a lack of exposure to information from schools, especially learning materials about proper and correct hand washing. School-age children are an age that is prone to various diseases, such as diarrhoea and worms. in 2018 the number of cases of diarrhoea in East Kolaka was 593. The largest cases of diarrhoea in East Kolaka District were in Lambandia District, with 187 cases of diarrhoea, the majority of which occurred in school-age children. To find out the effect of video and simulation counselling on children's knowledge about washing hands with soap at the Lambandia District Elementary School, East Kolaka. Methods: This study uses a quantitative research design with a quasi-experimental research design. This research was conducted in three SDN Lambandia District. The study population was school children with a sample of 70 children who were divided into two experimental groups and one control group. Sampling was done by a proportionate random sampling method. Result: The findings show from statistical tests that there is an effect of video and simulation on children's knowledge. This can be seen from p-value both of them are 0.000 < = 0.05. Conclusion: There was an effect of video screening and simulation on children's knowledge about washing hands with soap at the Lambandia District Elementary School, East Kolaka Regency.